Attitudes Toward Chiropractic: A Survey of Canadian Obstetricians. (April 2016) - Weis, Carol Ann; Stuber, Kent; Barrett, Jon; Greco, Alexandra; Kipershlak, Alexander; Glenn, Tierney; Desjardins, Ryan; Nash, Jennifer; Busse, Jason
We assessed the attitudes of Canadian obstetricians toward chiropractic with a 38-item cross-sectional survey. Ninety-one obstetricians completed the survey, for a response rate of 14% (91 of 659). Overall, 30% of respondents held positive views toward chiropractic, 37% were neutral, and 33% reported negative views. Most (77%) reported that chiropractic care was effective for some musculoskeletal complaints, but 74% disagreed that chiropractic had a role in treatment of non-musculoskeletal conditions. Forty percent of respondents referred at least some patients for chiropractic care each year, and 56% were interested in learning more about chiropractic care. Written comments from respondents revealed concerns regarding safety of spinal manipulation and variability among chiropractors. Canadian obstetricians' attitudes toward chiropractic are diverse and referrals to chiropractic care for their patients who suffer from pregnancy-related low back pain are limited. Improved interprofessional relations may help optimize care of pregnant patients suffering from low back pain.